Citrus pomace fermentation with autochthonous probiotics improves its nutrient composition and antioxidant activities. (1st March 2022) - Hu, Xi; Zeng, Jiarui; Shen, Fei; Xia, Xuesen; Tian, Xiaofei; Wu, Zhenqiang
Abstract: This study was aimed at improving the nutrient composition of citrus pomace by solid-state fermentation with the autochthonous probiotics Lactobacillus plantarum P10, M14 and Bacillus subtilis BF2. The results showed that B. subtilis plays an important role in the release of phenolic components during fermentation, by increasing the cellulase, filter paperlyase, and pectinase activities. Co-fermentation with B. subtilis BF2 and L. plantarum P10 (BPF) increased the total phenolic content of CP by up to 133.15%, while single-bacteria fermentation with L. plantarum M14 significantly increased dietary fiber and organic acid content by 47.06% and 1429%, respectively. Furthermore, the phenolic fractions were markedly changed after fermentation, naringin and hesperidin were the main phenolic compounds in CP. They were highly correlated ( r  > 0.85, p  < 0.05) with DPPH and ABTS + radical scavenging abilities, which increased by 397.8% and 226.1%, respectively, when BPF was used. This study provides a potential method for producing high-value food or feed materials, with high antioxidant activities, from CP. Graphical abstract: Image 1 Highlights: Three kinds of autochthonous probiotics were isolated from citrus pomace (CP). Fermentation with probiotics improved CP's dietary fiber and organic acid contents. Phenolics and antioxidant activities were much enhanced by probiotic fermentation. Co-fermentation increased the naringin and hesperidin content in CP. CMCase, FPase, and pectinase played key roles in fermentation synergism.